Potentially Common Therapeutic Targets for Multiple Sclerosis and Ischemic Stroke - Paternò, Roberto; Chillon, Jean-Marc (Frontiers in Physiology, 2018)
Ischemic stroke (IS) and multiple sclerosis (MS) are two pathologies of the central nervous system (CNS). At the first look, this appears to be the only similarity between the 2 diseases, as they seem quite different. Indeed IS has an acute onset compared to MS which develops chronically, IS is consecutive to blood clot migrating to cerebral blood vessels or decrease in cerebral blood flow following atherosclerosis or decreases in cardiac output whereas MS is an immune disease associated with neurodegeneration. However, both pathologies share similar pathologic pathways and treatments used in MS have been the object of studies in IS. In this mini-review we will discuss similarities between IS and MS on astrocytes and neuroinflammation hallmarks emphasizing the potential for treatments.